Penanganan Pembiayaan Gadai Bermasalah pada BMT Syariah NU Ngasem Kantor Cabang Paron Kabupaten Ngawi - Sulandari, Siti; Kasmiati, Kasmiati (LABATILA : Jurnal Ilmu Ekonomi Islam, 2024)
Financing is funding provided by one party to another party to support planned investments. In Sharia banking financial institutions, financing is an asset whose quality must be assessed based on the principle of prudence. Rahn is a form of debt and receivable agreement, which gains the trust of the person who owes the debt. Rahn Tasjily financing is a contract which guarantees an item for someone's debt, where the agreement between both parties states that the borrower only submits legal proof of ownership to the collateral recipient (murtahin), so that the physical collateral of the item remains in the control and use of the collateral provider. (rahin). Realization of financing is not the last stage of the financing process because it is impossible for a long period of time without financing problems to occur. The main problem in this research is the handling methods applied by BMT in an effort to resolve problematic financing. The type of research used is qualitative research, namely field research. Data collection methods through interviews and documentation. From the results of this research, it can be seen that resolving problematic financing at BMT NU Ngasem Paron branch uses three methods, namely the approach method, Restructuring, and rescheduling.Keywords: Rahn, problematic financing, resolution